2011
DOI: 10.1037/a0019957
|View full text |Cite
|
Sign up to set email alerts
|

Why it is too early to lose control in accounts of item-specific proportion congruency effects.

Abstract: The item-specific proportion congruency (ISPC) effect is the finding of attenuated interference for mostly incongruent as compared to mostly congruent items. A debate in the Stroop literature concerns the mechanisms underlying this effect. Noting a confound between proportion congruency and contingency, Schmidt and Besner (2008) suggested that ISPC effects are entirely contingency based. We introduce a broader theoretical analysis that points to the contribution of both contingency and item-specific control me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
349
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(400 citation statements)
references
References 35 publications
47
349
4
Order By: Relevance
“…As discussed in the introduction, this is due to the fact that contingency has more time to influence responding on incongruent relative to congruent trials. The degree to which the results do or do not deviate from additivity can be altered by playing with parameters, many of which might correspond to differences between experiments (e.g., speeding target identification, similar to Bugg et al, 2011). Deviation from additivity was also found with an earlier version of the model that more closely corresponded to the response threshold idea of Schmidt and Besner (2008).…”
Section: (Figure 3 About Here) Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As discussed in the introduction, this is due to the fact that contingency has more time to influence responding on incongruent relative to congruent trials. The degree to which the results do or do not deviate from additivity can be altered by playing with parameters, many of which might correspond to differences between experiments (e.g., speeding target identification, similar to Bugg et al, 2011). Deviation from additivity was also found with an earlier version of the model that more closely corresponded to the response threshold idea of Schmidt and Besner (2008).…”
Section: (Figure 3 About Here) Discussionmentioning
confidence: 91%
“…However, there is a problem with the prediction that contingency and congruency should always be additive. Even if it is true that contingency and congruency effects are due to independent processes, it does not necessarily follow that the two effects will be perfectly additive (and, indeed, they are not in all task variants; e.g., Bugg, Jacoby, & Chanani, 2011). For example, incongruent trials take longer to respond to than congruent trials, so there is more time on an incongruent trial for contingencies to bias responding relative to a congruent trial.…”
Section: Adaptation In the Item-specific Proportion Congruent Paradigmmentioning
confidence: 99%
“…Support of this notion came with the observation that contingency learning and congruency effects are additive. While this additive pattern has been observed elsewhere (e.g., Atalay & Misirlisoy, 2012), deviations from additivity are also sometimes observed (e.g., Blais & Bunge, 2010;Bugg, Jacoby, & Chanani, 2011). For instance, in a word-picture Stroop task, Bugg and colleagues observed that incongruent trials were more influenced by item PC (and thus contingency) than congruent trials.…”
Section: Item-specific Proportion Congruentmentioning
confidence: 86%
“…Future work might aim to explore whether our simple learning account is sufficient, or whether attentional adaptation to conflict plays an additional role in these phenomena. This is already a heated debate in the attentional control literature (Atalay & Misirlisoy, 2012;Bugg, Jacoby, & Chanani, 2011;Crump & Milliken, 2009;Hazeltine & Mordkoff, 2014;Levin & Tzelgov, 2016;Notebaert & Verguts, 2007;Schmidt, De Schryver, & Weissman, 2014;Schmidt et al, 2015) and the PEP model might serve as a useful reference for how far one can go with episodic learning alone.…”
Section: Conflict Monitoring and Attentional Adaptationmentioning
confidence: 99%